2022
DOI: 10.1039/d2nr03544h
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan self-assembly yields cytotoxic nanofibers containing amyloid-mimicking and cross-seeding competent conformers

Abstract: Dietary consumption of Trp via protein-based foods is essential for the maintenance of crucial metabolic processes including the synthesis of proteins and several vital metabolites such as serotonin, melatonin, Acetyl...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 72 publications
2
23
0
Order By: Relevance
“…One important advantage of this protocol is that the incorporated fluorophores do not leach from the nanofibers during prolonged storage or after serial dilutions, and this property would greatly benefit the cellular studies on amyloid aggregates. Furthermore, several studies on the self-assembly of single metabolites (e.g., Tyr, Trp, and Phe) into amyloid-like fibrils [14][15][16]32,38 have become highly relevant to the pathophysiology of metabolite-associated diseases such as PKU, tyrosinemia and hypertryptophanemia. Unlike covalent-conjugation of fluorophores, our method of non-covalent incorporation of fluorophores could offer a better strategy for making fluorescent fibrils generated from metabolite self-assembly, as evident from our studies on Rho-B-incorporated dopamine nanostructures (Fig.…”
Section: Application Of Rho-b-incorporated Amyloids For Experiments I...mentioning
confidence: 99%
“…One important advantage of this protocol is that the incorporated fluorophores do not leach from the nanofibers during prolonged storage or after serial dilutions, and this property would greatly benefit the cellular studies on amyloid aggregates. Furthermore, several studies on the self-assembly of single metabolites (e.g., Tyr, Trp, and Phe) into amyloid-like fibrils [14][15][16]32,38 have become highly relevant to the pathophysiology of metabolite-associated diseases such as PKU, tyrosinemia and hypertryptophanemia. Unlike covalent-conjugation of fluorophores, our method of non-covalent incorporation of fluorophores could offer a better strategy for making fluorescent fibrils generated from metabolite self-assembly, as evident from our studies on Rho-B-incorporated dopamine nanostructures (Fig.…”
Section: Application Of Rho-b-incorporated Amyloids For Experiments I...mentioning
confidence: 99%
“…The cytotoxicity of the membrane was evaluated in terms of optical density (OD) values by using a methyl thiazolyl tetrazolium (MTT) assay. , A 30 cm 2 sample was immersed in 10 mL of DME/F-12 medium and cultured in a CO 2 incubator at 37 °C for 24 h, and then the leaching liquor was obtained by filtering with a disposable needle filter (Millipore 0.22 μm). L-929 cells were used in the experiments.…”
Section: Methodsmentioning
confidence: 99%
“…The fibers here reported could find application as cytotoxic compounds, similar to higher ordered structures formed by aromatic metabolites or tryptophan that exert neurotoxic action. 21 In addition, fibers could be employed for the production of new biomaterials, such as hydrogel to be applied in tissue engineering.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…In physiological conditions tryptophan self-assembles into cytotoxic nanofibers, characterized by amyloid mimicking and cross-seeding conformers. 21 Co-assembly of D and L racemic mixtures of tryptophan yields rigid supramolecular materials with aromatic rings packed in a knob-to-hole fashion. 22 It is reported that conjugation of the WW peptide to a DNA 12-mer results in the formation of aggregates, whose morphology is concentration-dependent.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation